Severe incisor resorption by impacted maxillary canines: case report and literature review - S. J. NUTE (Paediatric Dentistry, 2004)
This paper reviews the literature relating to incisor resorption caused by impacted maxillary canines, and describes the presentation and management of a patient with unusually severe early resorption. This case highlights the need for careful monitoring of maxillary canine eruption for all paediatric patients.